Investigación sobre resolución de problemas matemáticos - Fernández Bravo, José Antonio (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2002)
It is nowadays rather common to speak about scientific proposals whenever there is any reference to the acquisition of some knowledge by contrasting ideas. That is why it is utterly needed to be able to think and work on the scientific field in which any project is set. This research attempts to be a contribution to the study of mathematics problem solving at primary school, through the invention-reconstruction of problematic situations by the students. This training must allow the students to reach the acquisition of concepts by means of their own discoveries. The specific terminology and the accurate must be the finish line in the building of knowledge of knowledge, and not the starting point.